EFEKTIVITAS ATOMIC HABITS TERHADAP PENINGKATAN MAHARAH KALAM PESERTA DIDIK PROGRAM BILINGUAL SMA TAKHASSUS AL-QUR’AN KALIBEBER WONOSOBO - sunarko, asep; Astri Dyah Anggraini, Dwi (Tarling : Journal of Language Education, 2023)
This research aims to evaluate and determine the level of effectiveness of implementing atomic habits created by James Clear in improving the maharah kalam proficiency of bilingual students at Takhassus Al-Qur'an High School Kalibeber Wonosobo. Maharah kalam proficiency involves students' speaking abilities using and expressing themselves verbally in Arabic. This research adopts a quantitative approach with the aim of collecting data that can be measured numerically and analyzing it statistically. This research used a one group pretest-posttest design, where in this research only one group or one class was used. The subjects of this research were 20 bilingual students at Takhassus Al-Qur'an High School Kalibeber Wonosobo. This research uses two variables, namely the independent variable and the dependent variable. The independent variable is the application of atomic habits, while the dependent variable is the increase in anger at bilingual students at Takhassus Al-Qur'an High School Kalibeber Wonosobo using several data collection techniques, namely, observation, interviews involving bilingual dormitory supervisors and bilingual students at Takhassus Al High School. -Qur'an Kalibeber Wonosobo, pretest-posttest test and documentation. The results of the pretest-posttest research which was carried out by means of an oral test with a total of 8 pretest questions and 15 posttest questions were then processed, analyzed and then compared using the normality test, t-test and N-Gain test to determine the level of difference, improvement and effectiveness of increasing anger. in bilingual students.